The Lombard laws - Drew, Katherine Fischer (Sources of medieval history., 1973)
Here presented for the first time in English are the law codes of the Lombard kings who ruled Italy from the sixth to the eighth centuries. The documents afford unparalleled insight into the structure and values of Germanic society.